An Ecological and Identification Study for Algae in Groundwater of Selected Area in Tikrit city and It’s Surrounding Area (Baghdad Science Journal, 2014)
The present study is carried out to identify the algae in the groundwater of the three areas of Tikrit city, including (the center of Tikrit , the region of AL-Jazira , Awainat village) by nine wells, a depths ranged between 9 meter at well 8 and 110 meter at wells 3 and 5 . And examined the environmental characteristics of physical, chemical and biological factors during the study period from September 2009 to June 2010. It is obtained that wells in the study area is lower alkalinity, average it ranged (6.448-7.418). It was noted that the values of the dissolved oxygen are few and almost non-existent in some cases it ranged between (6.5-6.3)mg/l , analysis of biological oxygen demand refers to wells water (clean- very clean) average it ranged between (1420-1990)mg/l . Reason of groundwater very hardness due to geological factors of study area, which was mostly the result of ion bicarbonates, and recorded rate values of sulphates (258.2-406.2)mg/l. As for plant nutrients, the values of silica were relatively high (7.07-10.935)mg/l .While the concentration of active nitrite ions and phosphate, were random during the study period, it ranged between(0.128-2.979),(0.564-2.065)mg/l respectively. The biological side of this involved the identifying of algal in the studies wells. Diatoms formed the highest majority of plan plankton in the study area, the ratio of diatoms was 48%, then the Chlorophyceae was 32.4%, and the ratio of Cyanophyceae was 14.2%, and lastly the Euglenophyceae was 5.1%. Chlorophyll values were relatively high , the values of chlorophyll a was lower from chlorophyll b , c values .That’s indicate dominated species of organisms in the study area. The results indicated analysis to limit many effect factors on concentration of chlorophyll in algae in the study area